Botanical Agents for the Treatment of Nonmelanoma Skin Cancer. (24th July 2013) - Millsop, Jillian W.; Sivamani, Raja K.; Fazel, Nasim
Abstract : Nonmelanoma skin cancers, including basal cell carcinoma and squamous cell carcinoma, are common neoplasms worldwide and are the most common cancers in the United States. Standard therapy for cutaneous neoplasms typically involves surgical removal. However, there is increasing interest in the use of topical alternatives for the prevention and treatment of nonmelanoma skin cancer, particularly superficial variants. Botanicals are compounds derived from herbs, spices, stems, roots, and other substances of plant origin and may be used in the form of dried or fresh plants, extracted plant material, or specific plant-derived chemicals. They possess multiple properties including antioxidant, anti-inflammatory, and immunomodulatory properties and are, therefore, believed to be possible chemopreventive agents or substances that may suppress or reverse the process of carcinogenesis. Here, we provide a review of botanical agents studied for the treatment and prevention of nonmelanoma skin cancers.